Digital psychosocial interventions for individuals with spinal cord injury: a scoping review - Armstrong, Alice; Oetinger, Katja; Weimer, Katja; Hönig, Klaus (Frontiers in Psychiatry, 2024)
OBJECTIVE: To provide an overview of the digital mental health care landscape for individuals with spinal cord injury (SCI). METHODS: PubMed, PsycInfo, and PSYNDEX were searched for articles meeting the following criteria: (1) article written in English or German; (2) digital psychosocial intervention; (3) SCI only; (4) treatment of individuals with SCI and not their relatives or caregivers. Records were screened by title and abstract and records meeting the inclusion criteria were obtained for full text screening. The references of identified articles were screened to find further relevant articles. The literature search was updated before submission. Risk of Bias was assessed by using the Cochrane risk-of-bias tool for randomized trials (RoB 2) and a narrative synthesis was conducted.RESULTS: Ten randomized-controlled trials (RCT) and ten non-randomized-controlled trials were identified and compared in this review, evaluating twelve internet-and mobile-based interventions, five smartphone apps, and three virtual reality applications. The interventions were primarily used as stand-alone aftercare programs. While some were not based on any theory, cognitive behavioral therapy mostly served as the theoretical basis for the online interventions. The extent of human support also varied greatly between the studies. The number of intervention modules ranged between 2 and 72. There were also major differences in outcome variables and effects. A meta-analytical evaluation of the data was not conducted due to heterogeneity of studies.CONCLUSION: Digital applications to promote the psychosocial health of individuals with SCI are an emerging field of research with many treatment approaches still to come. First high quality RCT studies report promising results. Unfortunately, not all studies are of high quality or the interventions have been insufficiently adapted to the needs of people with SCI. Therefore, more research is needed to further develop applications, and to generalize and test the effects found in the long term.